Invasive hemodynamic monitoring for fluid management in septic shock patients - TAŞKIN, Öztürk; DAŞ, Ayşe Nur; BALCI, Canan (MediHealth Academy, 2022)
Aim Sepsis is still one of the most common causes of death, despite advances in treatment and technologies. Invasive monitoring in sepsis can improve survival. In this study, we aimed to compare the efficacy of hemodynamic monitoring in the fluid treatment of patients with septic shock. Material and Method Forty septic shock patients were divided into two groups. Group I (n = 20) was monitored with central venous pressure, and Group II (n = 20) with a cardiac output device (EV1000). Arterial blood gases were analyzed four times daily for the groups, and lactate values, diuresis status, need for dialysis, and inotrope need was recorded. For Group I, the central venous pressure and mean arterial pressure values were recorded for group II, cardiac output, cardiac index, stroke volume, stroke volume index, and mean arterial pressure values. Results There was a significant difference between the mean arterial pressures of the groups on the 1st and 2nd days (p = 0.034 and p = 0.026, respectively). In Group II, mean arterial pressures were higher on days 1 and 2. There was no significant difference between the other data recorded. Conclusion We observed no significant difference between central venous pressure monitoring and invasive monitoring in septic shock patient follow-up.
Keywords: 3. Good health